Reduced enriched compost and fertilizer inputs improve soil properties and GP3 pineapple performance on degraded Ultisols - Sari, Reny Mita; Putra, Eka Tarwaca Susila; Sulistyaningsih, Endang; Kurniasih, Budiastuti; Ziaurrahman, Ahmad (Journal of Degraded and Mining Lands Management, 2026)
This study evaluated whether reducing the dose of soil amendment and enriching it with vermicompost and biochar could maintain soil properties and support the growth of pineapple (Ananas comosus (L.) ‘GP3’) cultivated on degraded Ultisols. This experiment aimed to assess the effect of reducing the dose of soil amendment and decreasing the inorganic fertilizer application to 75% of the recommended dose on soil properties, nutrient uptake, and plant growth. The experiment used a split-plot design with varying doses of enriched compost combined with vermicompost and biochar, and two levels of inorganic fertilizer (75% and 100% of the recommended dose). Soil properties, nutrient uptake, and plant growth were measured and analyzed using Dunnett's test at ? = 0.05. The results showed that reducing the dose of enriched compost and decreasing the inorganic fertilizer by 25% generally resulted in soil properties, nutrient uptake, and plant growth comparable to those obtained using a higher dose of compost only and a full dose of inorganic fertilizer. Soil properties indicators generally remained stable across all treatments, with a small and transient decrease in soil nitrogen, which only occurred in the 25CVB1 treatment at later stages of plant growth. Although Ca and Mg uptake in the 25CVB3 treatment was lower at 4 months after planting, at 8 months after planting, the uptake levels were comparable across all treatments. These findings indicate that compost enriched with vermicompost and biochar allows for reduced doses of soil amendment and inorganic fertilizers without compromising soil quality or pineapple growth, thus providing a sustainable and cost-effective management strategy for pineapple cultivation on Ultisols.